Gender and Equality in Muslim Family Law, Justice, and Ethics in the Islamic Legal Tradition: By Ziba Mir-Hosseini, Kari Vogt, Lena Larsen, and Christian Moe, eds. (New York: I.B. Tauris, 2013. 320 pages.) (American Journal of Islam and Society, 2014)
In the aftermath of the Arab Spring, some advocated a turn toward “tradition,”thereby raising fears that women would be pushed out of the public arena despitetheir active participation and would even lose those gains made underprevious governments. The debates around gender parity vs. complementaritythat were stirred up were not new, but they did manage to acquire new cogencyin the context of the emotionally charged deconstruction of the old politicalsystem and the subsequent transition to new governments.The arguments made by both sides were often couched within a frameworkof liberal human rights or in terms of Islamic tradition. Gender andEquality in Muslim Family Law is a valuable contribution to the discussionon the apparent contradiction between these discourses and a learned attemptto bridge them. The editors of this collective book, which stems from a numberof workshops organized by the Oslo Coalition on Freedom of Religion or Belief,explore how gender equality, as shaped by contemporary ideas of humanrights, can be reconciled with the Islamic legal tradition, which is rooted inpre-modern conceptions of justice.In the first chapter, Mir-Hosseini examines the classical fiqhī understandingof gender justice by focusing on qiwāmah (guardianship of women), whichis enshrined in most Muslim family codes, and overviews twentieth-centuryreforms and codifications. She also discusses the ideas of al-Tahir al-Haddad(d. 1935) and Fazlur Rahman (d. 1988), two reformists who influenced subsequentdiscourses on equality in the family within an Islamic framework.Her contribution ends with a looks at the emergence of political Islam, transnationalfeminism, and non-governmental organizations (NGOs), all of whichadd a new dimension to preexisting debates.The rest of the book is divided into two sections. The first explores someconcrete efforts at legal reform and social activism that reconcile Islam andhuman rights. Mulki al-Sharmani delves into the concept of qiwāmah inEgyptian law and in courtroom practice, pointing out the legal strategiespursued by litigants and the disconnect between the model of marriage upheldby family codes and the actual practice of marriage. Marwa Sharafedinanalyzes Egyptian women’s rights NGOs and their discourse on personalstatus law that blend, to varying degrees, religious and human rights frames ...